Current directions for improving the administrative, legal and organisational principles of the activities of higher education institutions of the MIA of Ukraine which provide police training, taking into account the requirements of martial law (Bulletin of Kharkiv National University of Internal Affairs, 2023)
The authors have studied the legal and organisational framework for the activities of higher education institutions of the Ministry of Internal Affairs of Ukraine which provide police training. It has been determined that the state of war caused by Russia’s aggression against Ukraine imposes new requirements on the quality of staffing of all security and defence sector entities, in particular, the National Police of Ukraine. Today, police units take part in hostilities, are involved in stabilization and filtration measures, mine countermeasures, evacuation of the civilian population from the combat zone and adjacent territories. Policemen are also involved in providing assistance to the population in the liberated territories, delivering food and essential items to people who have survived the occupation in extremely difficult conditions.It has been proven that institutions of higher education with specific learning conditions, which train police officers, must quickly adapt to changes in the tasks and powers of the National Police, so that the skills and abilities of students of higher education meet not only the standards of higher education in the relevant specialties, but also the state of internal security environment of the state and new areas of activity of state law enforcement agencies in a special period.On the basis of the work carried out, conceptual directions for further improvement of the activities of these institutions of higher education have been formulated, taking into account the requirements of the martial law. The main areas that need appropriate optimization and transformation are as follows: the regulatory and legal support of the educational process and scientific activity, legal regulation of the work of the psychological service, as well as material and technical support of the service by those seeking higher education; the need to change industry standards of higher education and typical curricula and educational programmes for police training; the improving the content of special educational disciplines, and changing approaches to the formation of personnel.
Keywords: institution of higher education; institution of higher education with specific learning conditions; educational process; scientific activity; standard of higher education; Ministry of Internal Affairs of Ukraine; National Police; police officer.